When Hot and Cold Collide in Radical Change Processes: Lessons from Community Development - Fiol, C. Marlene; O'Connor, Edward J. (Organization Science, 2002)
A group's tendency to protect its identity often inhibits it from initiating radical change. For this reason, external interventions are typically needed to engage a group in reexamining and moving beyond its current identity. If threatened by these external interventions, however, identity beliefs can become emotionally heated and resistant to the cognitively rational efforts of outsiders. At the same time, the insider group's emotional energy is essential to mobilize and sustain radical change. This paper draws on community development theories and practices, as well as identity theories, to develop a model that traces the dynamic processes by which hot emotional interpretations and relatively colder cognitive interpretations interact to initiate, mobilize, and sustain radical change. It highlights the roles that emotion and cognition play as both barriers and essential facilitators of the change at different stages of the process, and proposes a set of strategies for managing them.